The system of civil procedural relations - Didenkо, L. V.; Andreichenko, S. S.; Chebotareva, G. V.; Kizlova, O. S. (Lviv-Toruń : Liha-Pres, 2019)
The article deals with the analysis of the definition of civil procedural relations. Investigates the model of “system of civil procedural relations”. The author states that today the most appropriate and relevant is the concept – the model of the system of civil procedural relations. The author examines the features of the modern model of the system of civil procedural relations. Notes that the content of the concept of such a model clearly demonstrates the use of all historical background since pre-revolutionary times. The author provides a classification of civil procedural relations. The author emphasizes that the system of civil procedural relations is independent and individual for each specific case.
Didenko L. V. The system of civil procedural relations. Juridical scholarly discussions as a factor for the sustainable development of legal doctrine and legislation : collective monograph / S. S. Andreichenko, G. V. Chebotareva, L. V. Didenko, O. S. Kizlova, etc. Lviv-Toruń : Liha-Pres, 2019. - P. 36-50.
Keywords: concepts of research of the system of civil procedural relations; modern model of the system of civil procedural legal relations